2000
DOI: 10.1054/jhsb.2000.0361
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Self-Administered Boston Questionnaire and Electrophysiological Findings in Follow-Up of Surgically-Treated Carpal Tunnel Syndrome

Abstract: A prospective study of electrophysiological examination and the Boston self-administered questionnaire (BQ) was carried out in patients with surgically-treated carpal tunnel syndrome. There were 104 hands in 93 patients (13 men and 80 women, mean age 56 years). The BQ was used to assess the severity of symptoms and function, and nerve conduction studies were done before surgical release by short incision at the palm, and at follow-ups 1 and 6 months after surgery. The BQ severity score improved or became norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
87
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 17 publications
18
87
2
3
Order By: Relevance
“…who found that shortly after CTR; improved NSV and NML is accompanied by changes in compound muscle action potential (CMAP) with further improvement at 6 month post operatively. Similar results were shown in study conducted by Mondelli M et al 2000 [15] . NMV and NSV were significantly improved as early as 1 month post operatively and the NSL and NML improve much at 3 month, 6 month respectively.…”
Section: Discussionsupporting
confidence: 91%
“…who found that shortly after CTR; improved NSV and NML is accompanied by changes in compound muscle action potential (CMAP) with further improvement at 6 month post operatively. Similar results were shown in study conducted by Mondelli M et al 2000 [15] . NMV and NSV were significantly improved as early as 1 month post operatively and the NSL and NML improve much at 3 month, 6 month respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Similar reports have been reported by Dhong et al [14], as well as Dudley Porras et al [15]. However, Mondelli et al [16] and Demirci et al [17] did not show an association between the two parameters. BCTQ scale was used for subjective pain assessment in these reports.…”
Section: Discussionsupporting
confidence: 86%
“…The mean time to return to daily activities or work did not differ according to the type of surgical release used, but the results of partial excision were found to be superior to those of simple section. Although significant correlation between improvement in the nerve conduction velocities and clinical improvement could not be consistently demonstrated at follow-up in the previous studies, 25,28 our results could probably be more objective if we were able to perform electrophysiologic tests in all patients postoperatively.…”
Section: Discussionmentioning
confidence: 58%
“…The improvement rate after open section of the transverse carpal ligament ranges from 91 to 98 percent. 6,10,[25][26][27] In patients we treated with only simple section of the transverse carpal ligament, we found the improvement rate was 85 percent. Conversely, the improvement rate following partial excision was 97 percent, which was comparable to those of the previously reported series.…”
Section: Discussionmentioning
confidence: 81%